Tourism Village Development Based on Participatory Planning - Fardani, Irland; Verry Damayanti; Ernady Syaodih; Hani Burhanudin (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
The Bandung Regency Government plans to develop 100 tourist villages with the aim of accelerating the economic growth of the surrounding community. One of the potential tourist villages in Bandung Regency is Baros Village. Baros village has good potential to be developed, but there is no tourism planning for the village. In this study a participatory approach was used or in tourism it is better known as Community Based Tourism Development. The analysis used in this study is the 4A and SWOT analysis. From the results of the analysis carried out, it was found that the village of Baros has strengths in terms of various natural conditions and cultural values. The development of the tourism area is divided into 3 zones, namely the core zone, buffer zone and service zone.